2010
DOI: 10.1590/s1677-55382010000400011
|View full text |Cite
|
Sign up to set email alerts
|

Diminution of oxalate induced renal tubular epithelial cell injury and inhibition of calcium oxalate crystallization in vitro by aqueous extract of Tribulus terrestris

Abstract: Purpose: Recurrence and persistent side effects of present day treatment for urolithiasis restrict their use, so an alternate solution, using phytotherapy is being sought. The present study attempted to evaluate the antilithiatic properties of Tribulus terrestris commonly called as "gokhru" which is often used in ayurveda to treat various urinary diseases including urolithiasis. Materials and Methods:The activity of Tribulus terrestris was investigated on nucleation and the growth of the calcium oxalate (CaOx)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…The urolithiasis clinical treatment has been extensively studied with different herbs, otherwise, others studies demonstrated a potent inhibitory effect on CaOx crystal adhesion and endocytosis of folk plants, as Phyllanthus niruri, from South America, Africa in vitro and vivo models (1,2).…”
Section: Editorial Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The urolithiasis clinical treatment has been extensively studied with different herbs, otherwise, others studies demonstrated a potent inhibitory effect on CaOx crystal adhesion and endocytosis of folk plants, as Phyllanthus niruri, from South America, Africa in vitro and vivo models (1,2).…”
Section: Editorial Commentmentioning
confidence: 99%
“…Calcium oxalate stones are found in two different varieties, calcium oxalate monohydrate (COM) or Whewellite, and calcium oxalate dihydrate (COD) or Weddellite. COM, the thermodynamically most stable form, is observed more frequently in clinical stones than COD and has a greater affi nity for renal tubular cells, thus responsible for the formation of stones in the kidney (2). Crystal growth and agglomeration may be due to supersaturation with respect to stone forming constituents or the Purpose: Kidney stone is one of the most prevalent diseases worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal deposition is usually associated with cellular injury and caused a variety of changes in renal architecture that facilitate crystal retention. The interactions between injured tubular epithelial cells and oxalate crystals are considered to have a significant role in the development of urinary stones (Aggarwal et al, 2010;Bijarnia et al, 2008;Grover et al, 1990;Khan, 2004;Khan et al, 2000). PPE (100, 300 and 500 mg/kg), when compared with urolithiatic group, significantly restored the normal renal architecture as shown in Figure 1 D, E, and F respectively.…”
Section: Histopathological Studymentioning
confidence: 99%
“…Media was supplemented with 1% Penicillin (100 units/mL)-Streptomycin (10,000 µg/mL) and 10% fetal bovine serum. Cells were cultured in 25 cm 2 tissue-culture treated flasks at 37º C and 5% CO 2 in humidified chambers (19).…”
Section: Cell Culturementioning
confidence: 99%